Predictors of prescription drug misuse among high school students in the United States - Nicholson, Jason (Deviant behavior, 2022)
The misuse of prescription medication is a prominent public health concern in the United States. The current study examines prescription drug misuse among adolescents under age 18, a segment of the population that is particularly vulnerable to this issue. The study further explores the correlates of prescription drug misuse among adolescents through analysis of the Youth Risk Behavior Survey results. The analysis is framed through Routine Activities Theory. Results indicate that aspects of the theory are moderate to strong predictors of youth prescription drug misuse.